A novel seed baiting technique for the epiphytic orchid Rhynchostele cervantesii, a means to acquire mycorrhizal fungi from protocorms - Cruz-Higareda, Jesús Bernardo; Luna-Rosales, Bárbara Susana; Barba-Álvarez, Amadeo (Lankesteriana: International Journal on Orchidology, 2015)
We developed a new and novel seed baiting technique sowing mature seeds of the epiphyitic orchid Rhynchostele cervantesii under natural conditions, We introduced a sponge in each package that may serve as a reservoir for water retention to benefit germination; In three of 22 packets we found protocorms in an early stage of development, six of wich were of sufficient size to warrant fungal isolations; Nine strains were isolated in pure culture and were inoculated on seeds and protocorms under in vitro conditions.